2020
DOI: 10.3390/molecules25102355
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Activity of Chiral Sulfonamides Based on the 2-Azabicycloalkane Skeleton

Abstract: A series of chiral sulfonamides containing the 2-azabicycloalkane scaffold were prepared from aza-Diels–Alder cycloadducts through their conversion to amines based on 2-azanorbornane or the bridged azepane skeleton, followed by the reaction with sulfonyl chlorides. The cytotoxic activity of the obtained bicyclic derivatives was evaluated using human hepatocellular carcinoma (HCC), medulloblastoma (MB), and glioblastoma (GBM) cell lines. Chosen compounds were shown to notably reduce cell viability as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The general approach to the evaluation of biological activity of investigated compounds followed the one described in our previous study on sulfonamides based on 2-azanorbornane skeleton [ 33 ]. All compounds were dissolved in dimethyl sulfoxide (DMSO).…”
Section: Resultsmentioning
confidence: 99%
“…The general approach to the evaluation of biological activity of investigated compounds followed the one described in our previous study on sulfonamides based on 2-azanorbornane skeleton [ 33 ]. All compounds were dissolved in dimethyl sulfoxide (DMSO).…”
Section: Resultsmentioning
confidence: 99%
“…According to the obtained results, the test substances are cytotoxic at high concentrations and long-term exposure but they are not genotoxic in human peripheral lymphocytes [23]. Samadaei et al (2020) reported the cytotoxic activity of chiral sulfonamides based on the 2-azabicycloalkane skeleton [24].…”
Section: (A) (B) (C) (D) (E) (F) (G) (H) (ı) (J) (K) (L) (M) (N) (O) (P) (R) (S)mentioning
confidence: 99%
“…The cytotoxic activity of the chiral sulfonamides was evaluated by human hepatocellular carcinoma, glioblastoma, and medulloblastoma cell lines. The compounds were shown to notably reduce cell viability as compared to nonmalignant cells [25]. The cytotoxicity of sulfonamide-based azaheterocyclic schiff base derivatives was performed on human keratinocyte and MCF-7 cell lines.…”
Section: Cytotoxic and Genotoxic Effectsmentioning
confidence: 99%